Implementation of Discipline Development for the State Civil Apparatus (ASN) as an Effort to Prevent Corruption - Mustika Sari, Dini (Master of Law Program, Ekasakti University, 2023)
Article 12 of Law of the Republic of Indonesia Number 5 of 2014 concerning the State Civil Apparatus stipulates that employees in their duties must be clean from corruption, collusion, and nepotism. The implementation of discipline development for the State Civil Apparatus (ASN) as an effort to prevent corruption crimes in the Agam Regency Regional Government is by disseminating to CPNS and ASN regarding anti-corruption behavior. Obligation to submit asset reports reported annually. Strengthening the internal integrity system of government agencies through various regional policies. The policy includes gratification control, conflict of interest handling, community complaint management through the Public Service Complaint Management System-People's Aspiration and Complaint Service (SP4N-LAPOR) channel which has been integrated with central and local government agencies. Control of corruption at the service unit level through the construction of Integrity Zones (ZI). Cooperation with the Central Statistics Agency (BPS) of West Sumatra Province conducts surveys regularly. The routine survey is aimed at determining public perceptions as service recipients regarding service quality and anti-corruption perceptions. Obstacles in the implementation of discipline development for the State Civil Apparatus (ASN) as an effort to prevent corruption crimes in the Agam Regency Regional Government include weak supervision and lack of guidance caused by the high volume of work and activities. The attitude of superiors who are too protective of their subordinates even though their subordinates commit deviations. Inadequate employee welfare factors. ASN is one of the things that must be considered by the Government. It is undeniable that they work to provide for the family. If they feel that their needs cannot be met optimally then they will try to get other jobs (side jobs) to meet their needs.